(untitled) (Global Journal of Human-Social Science, 2017)
The objective of this paper is to examine the prevalence of youth depressive symptoms and the association between ecological risk factors and youth depressive symptoms in the three Chinese contexts of mainland China, Hong Kong, and Taiwan. Papers included in this review were identified through electronic searches of the following databases: MEDLINE, Web of Science, JSTOR, ERIC, PsycINFO, and Google Scholar. Each database was searched from 2000 through 2015. Studies were selected if they evaluated the association between youth depressive symptoms and at least one ecological risk factors. In total, thirty-sevenarticles met criteria for inclusion and were incorporated in this review. The available research suggests Chinese youth are not immune to depressive symptoms, having prevalent rates ranging from 6% to 33%. Age, gender, cognitions, life events, family environment, family structure, family SES, parenting practices, academic performance, peer relationships, and relationships with teachers were associated with child and adolescent depressive symptoms in Chinese contexts.